Penentuan Resistansi Dinamis Pada Dioda Silikon 1n4002 Melalui Pengukuran Karakteristik Arus Terhadap Tegangan (I-V) Berbasis Arduino Mega 2560 - Pary, Tri Dewi Julianti; Latununuwe, Altje; Manuhutu, Fredrik; Kesaulya, Noke; Huliselan, Estevanus Kristian (Physikos: Journal of Physics and Physics Education, 2023)
An instrument for measuring I-V characteristics and determination of the dynamic resistance of a Silicon 1n4002 diode based on Arduino Mega 2560 has been successfully developed. This measurement was carried out by increasing the bias voltage periodically from 0 V to 5 V and observing the resulting forward voltage and forward current for each increase in the bias voltage. There is an increase in current when the diode voltage reaches 0.7 V, which is the diode barrier voltage. This happens if the limit resistor installed in the circuit is 100 Ω. The largest dynamic resistance value is 593.069 Ω, which is below the forward voltage of 0.6 V. Furthermore, the smallest dynamic resistance value is 2.293 Ω which is above the forward voltage of 0.7 V. The greater the value of the current flowing in the diode circuit, the smaller the dynamic resistance value of the diode and the smaller the value of the current flowing, the greater the dynamic resistance of the diode.